Accounting for Cultural Capital—Sustainability Agenda of Charities Serving the First Nations People towards Self-Determination—Evidence from the Northern Territory, Australia - Indra Abeysekera (Sustainability, 2022)
This study examined the role of the First Nations beneficiary charities in contributing to the 17 United Nations Sustainable Development Goals (SDGs) in the Northern Territory, Australia, as a way of attaining self-determination by closing the expectations gap between First Nations people and the mainstream Australians. Informed by the theory of self-determination (ethical and functional strands), a latent content analysis of 118 charities serving the First Nations people was conducted, coding the summary of their activities to ascertain their strategic engagement with the SDGs. A network analysis was also carried out to examine the charities’ connections with each other and their collective contribution towards the SDGs. The findings show that charities contribute to creating cultural capital through social capital, followed by intellectual capital dimensions. However, charities contributed little to building environmental capital dimension of the First Nations people. This study examined charities’ engagement with SDGs to build cultural capital in furtherance of self-determination of Australia’s First Nations people.